Widening participation in higher education with a view to implementing institutional change. (3rd July 2018) - Banerjee, Pallavi Amitava
ABSTRACT: In this research informed perspective, I discuss some of the barriers students face during progression to higher education. A crucial role can be played by higher education institutions (HEIs) and other public bodies. I discuss some of the measures taken and critically evaluate these to show how these can be improved. In the absence of a centralised admission system and autonomy exercised by HEIs, it is not clear yet how these targets will be achieved. HEFCE and OFFA play a vital role, but there is further scope towards addressing equality and diversity. This paper discusses some of the ways forward.